2014
DOI: 10.14191/atmos.2014.24.1.039
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Cloud Top Height Observed by a Ka-band Cloud Radar and COMS

Abstract: This study provides a comparative analysis of cloud top heights observed by a Ka-band cloud radar and the Communication, Ocean and Meteorological Satellite (COMS) at Boseong National Center for Intensive Observation of severe weather (NCIO) from May 25, 2013 (1600 UTC) to May 27. The rainfall duration is defined as the period of rainfall from start to finish, and the no rainfall duration is defined as the period other than the rainfall duration. As a result of the comparative analysis, the cloud top heights ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 26 publications
(24 reference statements)
0
9
0
Order By: Relevance
“…To evaluate the accuracy of ARM MMCR and GMS-5 satellite data over Manus Island, Hollars et al (2004) compared the cloud top heights calculated from each piece of equipment according to the type of cloud and precipitation. Oh et al (2014) performed a comparative analysis of CTHs observed by cloud radar and sensors onboard the Communication, Ocean, and Meteorological Satellite (COMS). They established that cloud radar was useful in detecting the CTH in the absence of precipitation.…”
Section: Introductionmentioning
confidence: 99%
“…To evaluate the accuracy of ARM MMCR and GMS-5 satellite data over Manus Island, Hollars et al (2004) compared the cloud top heights calculated from each piece of equipment according to the type of cloud and precipitation. Oh et al (2014) performed a comparative analysis of CTHs observed by cloud radar and sensors onboard the Communication, Ocean, and Meteorological Satellite (COMS). They established that cloud radar was useful in detecting the CTH in the absence of precipitation.…”
Section: Introductionmentioning
confidence: 99%
“…Attenuation occurs under heavy rainfall owing to the characteristics of cloud radar, and such attenuation increases as the rainfall intensity increases (Oh et al, 2014). Thus, in the present study, attenuation was calculated by using the high rain-rate cases (mean DV > DV thres ) to derive the A-R relationship.…”
Section: A-r Relationship For High Rain-rate Casesmentioning
confidence: 99%
“…Oh et al . (, ) conducted a comparative analysis on the cloud‐top height, observed with KaCR and COMS in the Boseong NCIO region. When precipitation did not occur, the cloud‐top heights were similar with the KaCR and the COMS.…”
Section: Kacr Reflectivity Correctionmentioning
confidence: 99%
“…However, this method can be used even with the KaCR alone. The cloud base height was observed by reflectivity from the KaCR (Oh et al ., , ). The rain rate was also obtained using the attenuation value of the cloud radar in recent studies (Matrosov, ; Chandra et al ., ).…”
Section: Z–lwc Relationships Based On the Kacr And The Mwrmentioning
confidence: 99%
See 1 more Smart Citation